Adaptive parenting strategies used by mothers with physical disabilities caring for infants and toddlers. (16th December 2018) - Powell, Robyn M.; Mitra, Monika; Smeltzer, Suzanne C.; Long‐Bellil, Linda M.; Smith, Lauren D.; Rosenthal, Eliana; Iezzoni, Lisa I.
Abstract: There is a paucity of information concerning adaptive parenting strategies utilised by mothers with physical disabilities, particularly during early motherhood. The purpose of this study is to describe the adaptive strategies used by mothers with physical disabilities during early motherhood. This qualitative study included semi‐structured telephone interviews between January and March 2014 with US mothers with a range of physical disabilities who had a baby within the past 10 years ( N  = 25). Interviews were audio‐recorded, professionally transcribed, and coded using content analysis. Analysis revealed five broad themes indicating important adaptive parenting strategies for mothers with physical disabilities caring for infants and toddlers: They are as follows: (a) acquiring or modifying baby‐care equipment, (b) adapting the home environment, (c) accessing information and supports, (d) developing communication strategies to facilitate safety, and (e) receiving assistance from others. This study indicates that mothers with physical disabilities employ a variety of adaptive strategies during early motherhood. The findings from the study suggest the need for more availability of supports and equipment for mothers with physical disabilities as well as information for prospective mothers with disabilities. In addition, healthcare and social work professionals must receive training about adaptive parenting strategies.